Can a psychosocial intervention programme teaching coping strategies improve the quality of life of Iranian women? A non-randomised quasi-experimental study. Issue 3 (25th March 2013) - Addelyan Rasi, Hamideh; Timpka, Toomas; Lindqvist, Kent; Moula, Alireza
Abstract : Objectives: To assess whether a psychosocial intervention teaching coping strategies to women can improve quality of life (QOL) in groups of Iranian women exposed to social pressures. Design: Quasi-experimental non-randomised group design involving two categories of Iranian women, each category represented by non-equivalent intervention and comparison groups. Setting: A large urban area in Iran. Participants: 44 women; 25 single mothers and 19 newly married women. Interventions: Seventh-month psychosocial intervention aimed at providing coping strategies. Primary outcome measures: Effect sizes in four specific health-related domains and two overall perceptions of QOL and health measured by the WHOQOL-BREF instrument. Results: Large effect sizes were observed among the women exposed to the intervention in the WHOQOL-BREF subdomains measuring physical health (r=0.68; p<0.001), psychological health (r=0.72; p<0.001), social relationships (r=0.52; p<0.01), environmental health (r=0.55; p<0.01) and in the overall perception of QOL (r=0.72; p<0.001); the effect size regarding overall perception of health was between small and medium (r=0.20; not significant). Small and not statistically significant effect sizes were observed in the women provided with traditional social welfare services. Conclusions: Teaching coping strategies can improve the QOL of women in societies where gender discrimination is prevalent. The findings require reproduction in studies with a more rigorous design before the intervention model can be recommended for widespread distribution.